Legal Protection of Indonesian Migrant Workers: International Law, National Regulations and Contemporary Problems - Hartono, Darminto; Samsuria, Indranila Kustarini (International Journal of Criminology and Sociology, 2021)
The research aims to focus on how to conduct an investigation of the regulations for the protections of Indonesian Migrant Workers (IMW) and what efforts are needed by the Indonesian government in addressing the problems for application of regulation. The method uses descriptive research with a qualitative approach through the normative juridical method and data analysis method. With the revised regulation videlicet Law No 18 of 2017, the Indonesian government will not only serve applicant of Indonesian migrant workers but also to their families. Furthermore, it will improve the quality of migrant workers along with protecting and providing safety for their families. The findings showed that Indonesian migrant workers as a legal subject have the rights to be protected and to oblige the requirements which is set by the Indonesian government as sending state and the government of destination state. Legal protection of Indonesian migrant workers in overseas required binding protection which is provided by the state.